Reducing Health-Care Associated Infections: An Organizational How-To Guide - Moynihan, Donald P.; Safdar, Nasia (My University, 2011)
The authors apply concepts of organizational theory to the empirical study of efforts to improve the safety of hospital patients. By identifying elements of efforts to improve safety, they outline a model of organizational change that charts how best to unfreeze an existing process, introducing a change and then freezing the change into a new process.